Credibility of TV news in a developing country: the case of Bangladesh - Andaleeb, Syed Saad; Rahman, Anis; Rajeb, Mehdi; Akter, Nasrin; Gulshan, Sabiha (© 2012 AEJMC., 2016)
This article was published in the Journalism and Mass Communication Quarterly [©2012 Published by AEJMC.] and the definite version is available at: http://doi.org/10.1177/1077699011430060 The Article's website is at: http://jmq.sagepub.com/content/89/1/73